2022
DOI: 10.7554/elife.77019
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of myelin proteome and oligodendrocyte transcriptome profiles between humans and mice

Abstract: Human myelin disorders are commonly studied in mouse models. Since both clades evolutionarily diverged approximately 85 million years ago, it is critical to know to what extent the myelin protein composition has remained similar. Here, we use quantitative proteomics to analyze myelin purified from human white matter and find that the relative abundance of the structural myelin proteins PLP, MBP, CNP, and SEPTIN8 correlates well with that in C57Bl/6N mice. Conversely, multiple other proteins were identified exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…To this aim, we surveyed the “BioGrid” protein–protein interaction database [ 31 ] and extracted the currently known list of experimentally demonstrated NDRG1 protein partners ( Table S7 ). Taking advantage of a recent study mapping the human CNS myelin proteome [ 32 ], we then crossed the NDRG1 interactome with the human myelin proteome ( Table S7 ). Interestingly, the list of NDRG1 protein partners was found to be highly significantly enriched in human myelin proteins (enrichment factor 6.24; p -value: 1.59 × 10 −40 ) ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…To this aim, we surveyed the “BioGrid” protein–protein interaction database [ 31 ] and extracted the currently known list of experimentally demonstrated NDRG1 protein partners ( Table S7 ). Taking advantage of a recent study mapping the human CNS myelin proteome [ 32 ], we then crossed the NDRG1 interactome with the human myelin proteome ( Table S7 ). Interestingly, the list of NDRG1 protein partners was found to be highly significantly enriched in human myelin proteins (enrichment factor 6.24; p -value: 1.59 × 10 −40 ) ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may indicate that surface trafficking of metabolite transporters in OLs is modulated by K + and Kir4.1-mediated signaling. Interestingly, proteome analysis of optic nerve lysates showed a reduction in proteins involved in intracellular membrane trafficking, including vesicle associated membrane proteins VAMP2 and VAMP3, as well as the small GTPases RAB2B and RAB5A, all of which are expressed by mature OLs [84][85][86] . While the molecular machinery regulating surface trafficking of metabolite transporters in OLs is still poorly understood, studies on adipocytes showed that VAMP2 and RAB5 family of GTPases are involved in GLUT4 glucose transporter trafficking [87][88][89] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although rodent models are commonly used to study the pathophysiology of human diseases, previous studies have demonstrated the difference between rodent and human nervous systems. For example, proteome and transcriptome studies identified multiple proteins exclusively or predominantly in human or mouse CNS myelin [ 61 ]. Even though both rat and human Schwann cells will proliferate in response to the axonal mitogen neuregulin, only the rat Schwann cells will efficiently ensheath and myelinate axons in vitro [ 62 ].…”
Section: Discussionmentioning
confidence: 99%